Y x 6,1 - y : 0,25 - y : 0,5 = 3,2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
y : 0,5 + y : 0,25 + y x 4 = 106,7
y x 2 + y x 4 + y x 4 = 106,7
y x (2+4+4)= 106,7
y x 10= 106,7
y= 106,7:10
y= 10,67
0,25 x y = 0,125 + 0,5
0,25 x y = 0,625
y = 0,625 : 0,25
y = 0,25
vậy x = ...
Ta có:
\(\left(x-0,5\right)^2+\left(y+0,25\right)^2=0\)
\(\Leftrightarrow x-0,5=y+0,25=0\)
\(\Leftrightarrow\left\{{}\begin{matrix}x=0,5\\y=-0,25\end{matrix}\right.\)
\(\left(x-0,5\right)^2+\left(y+0,25\right)^2=0\)
Do \(\hept{\begin{cases}\left(x-0,5\right)^2\ge0\\\left(y+0,25\right)^2\ge0\end{cases}\Rightarrow VT\ge0}\)
Dấu "=" xảy ra \(\Leftrightarrow\hept{\begin{cases}x-0,5=0\\y+0,25=0\end{cases}\Leftrightarrow\hept{\begin{cases}x=0,5\\y=-0,25\end{cases}}}\)
Vậy \(\hept{\begin{cases}x=0,5\\y=-0,25\end{cases}}\)
vì \(\hept{\begin{cases}\left(x-0,5\right)^2\ge0\\\left(y+0,25\right)\ge0\end{cases}}\)
mà \(\left(x-0,25\right)^2+\left(y-0,25\right)^2=0\)
\(\Rightarrow\hept{\begin{cases}\left(x+0,5\right)^2=0\\\left(y-0,25\right)^2=0\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}x+0,5=0\\y-0,25=0\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}x=-0,5\\y=0,25\end{cases}}\)
a ) y : 0.5 + y x 3 = 2,3
y x 2 + y x 3 = 2,3
y x ( 2 + 3 ) = 2,3
y x 5 = 2,3
y =0,46
b ) y : 0 , 25 - y : 2,5 = 0,18
y x 4 - y x \(\frac{2}{5}\) = 0,18
y x ( 4 - \(\frac{2}{5}\)) = 0 , 18
y x 3,6 = 0 , 18
y =0,05
Lời giải:
$y\times 6,1-y:0,25-y:0,5=3,2$
$y\times 6,1-y\times 4-y\times 2=3,2$
$y\times (6,1-4-2)=3,2$
$y\times 0,1=3,2$
$y=3,2:0,1=32$